Civil War Scoundrels and the Texas Cotton Trade. - Wilson, Walter E. (McFarland and Company, Inc. : McFarland, 2020)
"During the Civil War, scoundrels from both the Union and Confederate sides were able to execute illicit, but ingenious, schemes to acquire Texas cotton. Texas was the only Confederate state that bordered a neutral country, it was never forcibly conquered, and its coast was impossible to effectively blockade. Using little known contemporary sources, this story reveals how charlatans exploited these conditions to run the blockade, import machinery and weapons, and defraud the state's most prominent political, military and civilian leaders in the process. Best known for his role in the romantic entanglements of his co-conspirator William Sprague, Harris Hoyt stands out due to his sharp intellect and fascinating character. Hoyt was able to draw most of Abraham Lincoln's inner circle into his web of deceit and even influenced the impeachment of President Andrew Johnson. This is the first account to expose the depth and breadth of the many Texas cotton trading scams and the sheer audacity of the shadowy men who profited from them, but managed to escape the gallows." --Provided by publisher.